1998
DOI: 10.1021/ic980410c
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Cluster Assembly Using VO2(acac) as a Precursor:  cis-[VO(OCH(CH3)2)(acac)2], [V2O2(μ-OCH3)2(acac)2(OCH3)2], [V3O3{μ,μ-(OCH2)3CCH3}2(acac)2(OC2H5)], and [V4O4(μ-O)2(μ-OCH3)23-OCH3)2(aca

Abstract: The studies of an underexplored synthetic reagent, VO(2)(acac) (Hacac = acetylacetone) and semirational strategies for the formation of a complete series of simple vanadium(V) alkoxide clusters in alcohol-containing solvents. The neutral mono-, di-, tri-, and tetranuclear oxovanadium(V) complexes [V(2)O(2)(&mgr;-OCH(3))(2)(acac)(2)(OCH(3))(2)] (1), [V(4)O(4)(&mgr;-O)(2)(&mgr;-OCH(3))(2)(&mgr;(3)-OCH(3))(2)(acac)(2)(OCH(3))(2)].2CH(3)CN (2), [V(4)O(4)(&mgr;-O)(2)(&mgr;-OCH(3))(2)(&mgr;(3)-OCH(3))(2)(acac)(2)(OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 83 publications
(272 reference statements)
1
18
1
Order By: Relevance
“…This transformation was investigated in some detail by spectral measurements. When 2 was dissolved in CD 2 Cl 2 and analyzed by 1 H NMR, signals similar to those of the 4,4′- t Bubpy ligands in 3a and 3b were observed along with a broad singlet at δ 4.07 assigned to a terminal methoxido moiety (Figure c). 51 V NMR (CD 2 Cl 2 ) spectrum of 2 also showed signals similar to those of 3a and 3b (see Figure S8).…”
Section: Resultsmentioning
confidence: 85%
“…This transformation was investigated in some detail by spectral measurements. When 2 was dissolved in CD 2 Cl 2 and analyzed by 1 H NMR, signals similar to those of the 4,4′- t Bubpy ligands in 3a and 3b were observed along with a broad singlet at δ 4.07 assigned to a terminal methoxido moiety (Figure c). 51 V NMR (CD 2 Cl 2 ) spectrum of 2 also showed signals similar to those of 3a and 3b (see Figure S8).…”
Section: Resultsmentioning
confidence: 85%
“…The characteristic V═O stretching band of oxidovanadium(IV) complexes 1 – 3 appears at 1001, 978, and 997 cm −1 , respectively, [ 37,38 ] which is also present in the polymer‐grafted complexes 4–6 with slight shifting from the original position, confirming the presence of homogeneous complexes 1 – 3 in the polymer chain (shown in Figure 1).…”
Section: Resultsmentioning
confidence: 87%
“…The 51 V NMR spectrum from an approximately V(IV):pbH 2 = 1:1 solution at pH = 2 showed a signal at −443.3 ppm (Figure 6a), which was within the range for selected five- and six-coordinate V(V)–hydroxamato complexes at low pH values and also other V(V) complexes with O,O′ coordination, such as diols and α-hydroxycarboxylic acids. 6569 There were no signals attributable to polyoxovanadate species ([HVO 4 ] 3– , −557 ppm; [V 2 O 7 ] 4– , −571 ppm; [V 4 O 12 ] 4– ,–577 ppm) in the spectrum(70) which suggested that the signal was attributable to [V V O(pb)] + or [V V O(OH)(pb)].…”
Section: Resultsmentioning
confidence: 99%